2023
DOI: 10.3390/ijms24065649
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Biomarkers in a Living Donor Kidney Transplantation Cohort—Predictive Value on Graft Function

Abstract: Early non-invasive detection and prediction of graft function after kidney transplantation is essential since interventions might prevent further deterioration. The aim of this study was to analyze the dynamics and predictive value of four urinary biomarkers: kidney injury molecule-1 (KIM-1), heart-type fatty acid binding protein (H-FABP), N-acetyl-β-D-glucosaminidase (NAG), and neutrophil gelatinase-associated lipocalin (NGAL) in a living donor kidney transplantation (LDKT) cohort. Biomarkers were measured up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
(50 reference statements)
0
0
0
Order By: Relevance
“…It would be very interesting to study the influence of sex difference on the response to oxidative stress and/or mitochondrial maintenance. We also observed the influence of sex mismatch on biomarkers in a previous study concerning urinary biomarkers [32]. In general, our study demonstrated that various donor, recipient, and transplantation-related factors impacted the baseline or the change of mtDNA over time.…”
Section: Discussionsupporting
confidence: 73%
“…It would be very interesting to study the influence of sex difference on the response to oxidative stress and/or mitochondrial maintenance. We also observed the influence of sex mismatch on biomarkers in a previous study concerning urinary biomarkers [32]. In general, our study demonstrated that various donor, recipient, and transplantation-related factors impacted the baseline or the change of mtDNA over time.…”
Section: Discussionsupporting
confidence: 73%